PENGARUH ATRIBUT PRODUK WISATA DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN BERKUNJUNG PADA KAWASAN WISATA DI KABUPATEN KARO - Vina Maria Ompusunggu, S.Sos., MSP; Ramcan Agustinus Sitorus; Candro Siagian (Universitas Quality, 2023)
This study aims to determine and prove how much (1) the effect of tourism product attributes on visiting decisions, (2) the effect of electronic word of mouth on visiting decisions, this type of research is causative research, where this research describes and analyzes the relationships between one variable and another or how a variable affects another variable. The population in this study were all people who had visited or who were visiting the Karo Regency Tourism Area. The sample used was 100 people using accedental sampling technique. The types of data used in this study are primary data and secondary data. Data analysis techniques using descriptive and inductive analysis through multiple regression analysis using the SPSS version 21.0 program. The hypothesis was tested with the F test and t test at α = 0.05. The results of this study indicate that: (1) Tourist Product Attributes have a negative and significant effect on Visiting Decisions with a value of tit = -0.046 and sig = 0.591, (2) Electronic Word of Mouth (E-WOM) has a positive and significant effect on Visiting Decisions with a value of tit = 6.793 and sig = 0.000.